RE-OS ISOTOPIC ANALYSIS OF THE KALATONGKE CU-NI SULFIDE DEPOSIT, NORTHERN XINJIANG, NW CHINA, AND ITS GEOLOGICAL IMPLICATION - Han C.M.; Xiao W.J.; Mao Q.G.; Zhao G.C.; Qu W.J.; Du A.D. (My University, 2006)
The Kalatongke is a large Cu-Ni deposit in the southern part of the Altay orogenic belt, northwestern China. Rhenium and osmium isotopic analyses of Ni-and Cu-bearing sulfide minerals from the deposit have been used to determine the timing of mineralization, the source of osmium, and, by inference, the source of ore metals. Sulfide ore samples have osmium and rhenium concentrations varying in the ranges of 0.29 - 3.07 ppb, and 6.605 - 61.10ppb, respectively. Analyses of these data yield a six-point isochron with an age of 305 ± 15Ma. The age implies that the Cu-Ni sulfide deposit and other related magmatic deposits in the same area formed between the latest Carboniferous and Early Permian post-collisional extension in the Altay Shan. An initial 187Os/188Os ratio of 0.352 ± 0.044 (MSWD=2.1) and the δ34S of -3.5‰ to + 3.0‰ for the ores, as well as initial 87Sr/86Sr ratios of metalliterous intrusions that vary from 0.70375 to 0.70504, suggest a magmatic source for the ores, with the melts being dominated by mantle contributions. The data also indicate that the Kalatongke Ni-Cu deposit, like many other copper, gold, and nickel deposits within central Asia, is related to post-collisional extensional processes.
Keywords: CU-NI DEPOSIT; KALATONGKE; RE-OS ISOTOPIC DATING; XINJIANG; Палеозой::Пермская; Палеозой::Каменноугольная; Paleozoic::Permian; Paleozoic::Carboniferous